2019
DOI: 10.1002/ece3.5664
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationship of fat body endoreduplication and queen fecundity in termites

Abstract: Endoreduplication or nuclear genome replication without cell division is widely observed in the metabolically active tissues of plants and animals. The fat body cells of adult female insects produce abundant yolk proteins and become polyploid, which is assumed to accelerate egg production. Recently, it was reported that in termites, endopolyploidy in the fat body occurs only in queens but not in the other females; however, the relationship between the fecundity and ploidy level in the fat body remains unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 63 publications
4
25
0
Order By: Relevance
“…We observed a first upregulation of the vg gene. As recently suggested for other termite species 39 , polyploidy in the fat body of M. natalensis queens can boost their egg production by increasing protein synthesis, notably VG. In Drosophila, seven out of eight insulin-like peptides (DILPs) are mainly produced in the brain insulin-producing cells except for DILP6, which is produced in the fat body.…”
Section: Surprising Upregulation Of Iis Pathway Componentssupporting
confidence: 54%
“…We observed a first upregulation of the vg gene. As recently suggested for other termite species 39 , polyploidy in the fat body of M. natalensis queens can boost their egg production by increasing protein synthesis, notably VG. In Drosophila, seven out of eight insulin-like peptides (DILPs) are mainly produced in the brain insulin-producing cells except for DILP6, which is produced in the fat body.…”
Section: Surprising Upregulation Of Iis Pathway Componentssupporting
confidence: 54%
“…Concomitantly with the growth of colonies and coinciding with their development of physogastry, the imaginal fat body of virgin queens (QT0) with its canonical fat storage function becomes replaced by a royal fat body (QT4), which is highly oriented towards specific protein synthesis and secretion 40 . A comparative analysis of different termite species recently suggested that endopolyploidy (or nuclear genome replication without cell division) permits the rate of vitellogenin synthesis to increase 41 . Developmental changes in oogenesis might rely on endopolyploidy and we therefore determine the percentages of the nuclei count at each ploidy level (2C, 4C, and 8C) in the fat bodies of adult queens in five stages.…”
Section: Resultsmentioning
confidence: 99%
“…Although adult fat body cells of termite queens (and sometimes also kings) undergo endoreduplications [ 53 ], these are expected to be infrequent in Pr. simplex , belonging to termites with low fecundity and low adult abdominal growth [ 54 ]. In other words, in both the honeybee and termites, the telomerase activation in long-lived reproductives appears as independent of the actual rate of nuclear divisions, at least in some of the studied organs.…”
Section: Discussionmentioning
confidence: 99%